Information on medicinal uses of chuchuhuasi (Maytenus macrocarpa) from folk healers of the district of Santa María de Huachipa, Lurigancho, Lima – Peru: a qualitative study - Jiménez-Grados, Lyane (2020)
Objective: To inquire the main conditions, properties and ways of consumption of chuchuhuasi from a group of folk healers of the district of Santa María de Huachipa (Lima – Peru). There are studies of the medicinal uses of chuchuhuasi (Maytenus macrocarpa) in native communities of the Amazon known by the inhabitants and indicated by folk healers. However, information on the medicinal uses and properties of chuchuhuasi on the coast and in urban communities is rare. Materials and methods: Ten folk healers voluntarily participated in the study. An interview questionnaire was administered to inquire the use of chuchuhuasi (properties, adverse effects, contraindications and ways of consumption). The interview was recorded and then transcribed. Afterwards, the data was categorized by peers and defined by consensus. Results: The main conditions for consuming chuchuhuasi were respiratory tract (80 %) and osteotendinous junction problems. The most important properties of chuchuhuasi were its anti-inflammatory and aphrodisiac effects. Dizziness was reported as adverse effect. Chuchuhuasi was contraindicated in pregnancy, hypertension and diabetes. In addition, its main ways of consumption were as spirit, ointment and infusion. Conclusions: Information on the medicinal uses of chuchuhuasi was obtained from a group of folk healers of the district of Santa María de Huachipa (Lima – Peru). The main condition for consuming chuchuhuasi was respiratory tract problems, and its antiinflammatory properties were highlighted.